EMPOWERING WOMEN THROUGH ENTREPRENEURSHIP IN URBAN COMMUNITIES - Munirah, Munirah; Asfahani, Asfahani; Tamrin Fathoni; Cindy, Agustin Hanivia; Hasan, Zainol (Community Development Journal : Jurnal Pengabdian Masyarakat, 2024)
This community service activity addresses women's important socio-economic challenges in urban communities by empowering them through entrepreneurship. Despite their potential, many women face barriers such as limited access to financial resources, inadequate training, and gender bias that hinder their entrepreneurial ambitions. This service aims to equip women with the skills, knowledge, and resources necessary to succeed as entrepreneurs, encouraging economic independence and social empowerment. This activity uses participatory action research (PAR) methods, involving women as co-researchers to identify their specific needs and challenges. Based on these insights, specialized training programs were developed, focusing on critical entrepreneurial skills such as business planning, financial management, and marketing. Financial assistance in the form of microloans and grants is also provided to help women overcome initial financial obstacles in starting their businesses. The results of this service are very significant, and there is a significant increase in the number of women-owned businesses in the community, which has an impact on improving the economy of the participants and their families. Additionally, the project fosters a support network of women entrepreneurs who continue to share resources and support each other. This initiative also contributes to positive changes in society's attitudes towards women in business, encouraging increased gender equality and social inclusion. In conclusion, this service shows the effectiveness of a comprehensive and integrated approach to empowering women through entrepreneurship in urban communities